2012
DOI: 10.1016/j.ajhg.2012.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Combined Analysis of Genome-wide Association Studies for Crohn Disease and Psoriasis Identifies Seven Shared Susceptibility Loci

Abstract: Psoriasis (PS) and Crohn disease (CD) have been shown to be epidemiologically, pathologically, and therapeutically connected, but little is known about their shared genetic causes. We performed meta-analyses of five published genome-wide association studies on PS (2,529 cases and 4,955 controls) and CD (2,142 cases and 5,505 controls), followed up 20 loci that showed strongest evidence for shared disease association and, furthermore, tested cross-disease associations for previously reported PS and CD risk alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
241
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 307 publications
(248 citation statements)
references
References 62 publications
0
241
2
5
Order By: Relevance
“…Our understanding of the genetic architecture of psoriasis has increased rapidly due to genome-wide association studies (GWASs), which have identified more than 40 psoriasis susceptibility genes/loci [2][3][4][5][6][7][8][9][10][11][12][13] . However, the combined effect of these loci does not fully account for the observed genetic susceptibility to psoriasis, indicating that additional genetic factors remain to be discovered.…”
mentioning
confidence: 99%
“…Our understanding of the genetic architecture of psoriasis has increased rapidly due to genome-wide association studies (GWASs), which have identified more than 40 psoriasis susceptibility genes/loci [2][3][4][5][6][7][8][9][10][11][12][13] . However, the combined effect of these loci does not fully account for the observed genetic susceptibility to psoriasis, indicating that additional genetic factors remain to be discovered.…”
mentioning
confidence: 99%
“…3 During the past five years, genome-wide association studies (GWAS), primarily based on single nucleotide polymorphism markers, have identified many loci as potential psoriasis susceptibility regions. 4,5 Angiotensin-converting enzyme (ACE) is an important circulating enzyme in the renin-angiotensin-aldosterone system (RAAS). 6 ACE is expressed in a wide range of tissues including skin, vascular endothelium and immune cells.…”
mentioning
confidence: 99%
“…6 Large epidemiological studies have shown that the higher incidence of psoriasis in patients with schizophrenia and even in individuals with a family history of schizophrenia in both Chinese and European populations. [7][8][9][10]20 While we demonstrated a shared genetic etiology between these diseases, common environmental factors may still play a role in the disease coetiologies (e.g., stress event in epidemiological studies). 38,39 The additional role of environmental factors and how such environmental factors may influence genetic factors (i.e., gene × environment interactions) remains to be explored.…”
Section: Main Findings and Implicationsmentioning
confidence: 99%
“…[16][17][18] Given that most common disorders and traits have been shown to have a polygenic basis, many researchers have explored the possibility that many complex disorders and traits, including schizophrenia and psoriasis, actually share genetic determinants (i.e., are genetically correlated to some degree). [19][20][21][22][23][24][25][26] This trend appears to be even more pronounced in diseases of autoimmune origin. 27 In this light, we tested our hypothesis of a shared genetic basis of schizophrenia and psoriasis using large cohorts previously studied in independent GWAS.…”
Section: Introductionmentioning
confidence: 99%